2012
DOI: 10.1086/669254
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Pricing Behavior in Perishable Goods Markets: Evidence from Secondary Markets for Major League Baseball Tickets

Abstract: Sellers of perishable goods increasingly use dynamic pricing strategies as technology makes it easier to change prices and track inventory. This paper tests how accurately theoretical models of dynamic pricing describe sellers' pricing behavior in secondary markets for event tickets, which are a classic example of a perishable good. It shows that some of the simplest dynamic pricing models describe seller behavior very accurately, and they explain why sellers cut prices dramatically, by 40% or more, as an even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(60 citation statements)
references
References 40 publications
3
56
0
Order By: Relevance
“…Such a strategy is still compatible with price reductions, as long as these occur randomly and do not disrupt the overall increasing temporal trend of prices (Deneckere and Peck, 2012;Sweeting, 2012).…”
Section: Factors Expected To Be Positively Associated With Dynamic Prmentioning
confidence: 99%
“…Such a strategy is still compatible with price reductions, as long as these occur randomly and do not disrupt the overall increasing temporal trend of prices (Deneckere and Peck, 2012;Sweeting, 2012).…”
Section: Factors Expected To Be Positively Associated With Dynamic Prmentioning
confidence: 99%
“…Moreover, Su [2007, p. 735] shows that higher prices closer to departure 13 Lazear [1986] also finds decreasing prices over time in a simple two-period model. Moreover, Sweeting [2010] documents the existence of decreasing prices in online resale markets for Major League Baseball tickets.…”
Section: Iii(ii) Dynamic Pricing Estimatesmentioning
confidence: 99%
“…29 A similar pattern arises in the hotel industry: Lee et al (2009) showed that normalized average prices are nearly independent of the number of days before arrival. Sweeting (2010) shows that in the market for baseball tickets, prices are decreasing as the game day approaches, providing a puzzling counterexample to our theory.…”
Section: Empirical Implicationsmentioning
confidence: 73%